2013
DOI: 10.3748/wjg.v19.i42.7433
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between dysplastic nodule and early-stage hepatocellular carcinoma: The utility of conventional MR imaging

Abstract: In the follow-up for a cirrhotic nodule, increased signal intensity on T2WI may be a sign of malignant transformation. Furthermore, a noted loss of hyperintensity on T1WI and the detection of arterial enhancement might indicate further progression of the histological grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Therefore, it enables the assessment of tumor vascularity as well as other hepatocellular-specific properties within the tumor. Thus Gd-EOB-DTPA has been proven valuable in detection and differential diagnosis of focal liver lesions, especially between early HCC and dysplastic nodule(DN) [ 3 , 9 ]. As HCCs in different degree of differentiation retain variable degree of normal liver function, they could potentially be classified using Gd-EOB-DTPA [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it enables the assessment of tumor vascularity as well as other hepatocellular-specific properties within the tumor. Thus Gd-EOB-DTPA has been proven valuable in detection and differential diagnosis of focal liver lesions, especially between early HCC and dysplastic nodule(DN) [ 3 , 9 ]. As HCCs in different degree of differentiation retain variable degree of normal liver function, they could potentially be classified using Gd-EOB-DTPA [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2427]. In our experience, a high signal intensity on T2 should be certainly considered a sign of malignant transformation because it was encountered only in HCCs, although with a poor detection rate (53.3 %) [28]. Our study certainly has some limits.…”
Section: Discussionmentioning
confidence: 84%
“…In a report that classified the signal intensity of DWI into three stages (iso/slight, moderate, and obvious) in 254 resected HCC, the prevalence of well-differentiated HCC was high and that of moderately or poorly differentiated HCC was low in the iso/slight intensity imaging group compared to the obvious intensity imaging group: the pathology of well/moderate/poor HCC was 38.9%/57.4%/3.7% for the iso/slight intensity group and 5.8%/77.4%/16.8% for the obvious intensity group [18] . Other reports showed that DWI features were linked to poor differentiation on pathology, vascular invasion, and recurrence risk factor after resection of small HCC [19,20] .…”
Section: Daa-svr Hcc (N = 26)mentioning
confidence: 89%